2019
DOI: 10.3389/fphar.2019.00849
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Treatment of Staphylococcus aureus in Patients With Cystic Fibrosis

Abstract: Staphylococcus aureus is a ubiquitous human commensal pathogen. It is commonly isolated in cystic fibrosis (CF) patients and is considered one of the main causes of the recurrent acute pulmonary infections and progressive decline in lung function that characterize this inherited life-threatening multisystem disorder. However, the true role of S. aureus in CF patients is not completely understood. The main aim of this narrative review is to discuss the present knowledge of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 93 publications
0
24
0
Order By: Relevance
“…Antibiotic failure and recurrent infections in CF patients are of critical concern. CF patients with chronic S. aureus respiratory infections can have frequent respiratory exacerbations that require antibiotic treatments, and it is common for these patients to simultaneously receive multiple antibiotics to treat co-infecting bacteria, including MSSA, MRSA, and P. aeruginosa 43 . MER is frequently used to treat P. aeruginosa infections [44][45][46] , and the cephalosporin CPT is increasingly being used against MRSA infections [47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic failure and recurrent infections in CF patients are of critical concern. CF patients with chronic S. aureus respiratory infections can have frequent respiratory exacerbations that require antibiotic treatments, and it is common for these patients to simultaneously receive multiple antibiotics to treat co-infecting bacteria, including MSSA, MRSA, and P. aeruginosa 43 . MER is frequently used to treat P. aeruginosa infections [44][45][46] , and the cephalosporin CPT is increasingly being used against MRSA infections [47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infections are extremely common and cause lung deterioration and remodeling quite similar to those associated with ABPA [5]. Moreover, co-infections are frequent in CF patients and specific signs as well as symptoms are not pathognomonic of a definitive etiology [13,14]. On the other hand, M. pneumoniae is not frequently associated with pulmonary exacerbation in patients with CF [2] and recent studies have shown that it presents with clinical, laboratory and radiographic findings similar to those due to typical bacterial infections [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Along with inhaled antibiotic strategies for eradicating P. aeruginosa in CF patients, novel therapeutic protocols have been proposed for the eradication of MRSA or emerging Bcc pathogens. Numerous protocols for the early eradication of MRSA have been reported to prevent the negative clinical implications of MRSA colonization [ 80 ]. A recent systemic review published by Lo et al examined two trials with MRSA-infected patients; in both, the active treatment was oral trimethoprim and sulfamethoxazole associated with rifampicin, while the control arm was observational only [ 81 ].…”
Section: Antibiotic Strategies For Eradicating P Aerugimentioning
confidence: 99%